THE ROLE OF INDOOR SMART GARDENS IN THE DEVELOPMENT OF SMART AGRICULTURE IN URBAN AREAS - Mihailović, Branko Miodrag; Radosavljević, Katica; Popović, Vesna (Economics of Agriculture, 2023)
The increasing global population and urbanization have led to a growing interest in urban farming to provide sustainable food production. Indoor smart gardens, a new form of urban farming, have emerged as an innovative and technology-based solution to urban agriculture. This paper explores the role of indoor smart gardens in modern urban farming and their potential impact on food production, environmental sustainability, and human health. Consequently, comparison was used of traditional outdoor farming vs. indoor smart gardening. Also, a comparative study was conducted using the case study of two leading brands of indoor smart gardens: Aerogarden and Click & Grow. The research’s results show that smart gardens have significant potential to revolutionize urban farming practices and address the growing demand for food production in urban areas. Our review of the literature and case study showed that smart gardens can significantly increase food production, improve environmental sustainability, and enhance human health in urban areas.